Trastuzumab re-treatment following adjuvant trastuzumab and the importance of distant disease-free interval: the HERA trial experience - Metzger-Filho, Otto (Breast Cancer Res Treat, 2015)
This retrospective analysis conducted using data from patients enrolled onto the Herceptin Adjuvant has two objectives: The first is to evaluate the impact of the time interval between the end of adjuvant trastuzumab and distant recurrence (TDRI) upon overall survival (OS). The second is to describe the duration of trastuzumab-based regimens in the metastatic setting for patients previously treated with adjuvant trastuzumab. The first objective included 187 patients treated with adjuvant trastuzumab and diagnosed with distant recurrence at 4-year median follow-up. The second objective included data from questionnaires sent to investigators retreating patients with trastuzumab upon distant recurrence: 144 of 156 questionnaires were returned (93 %), and 90 patients were selected based on available clinical information and consent for subsequent studies. There was no statistically significant relationship between TDRI following 1 year of adjuvant trastuzumab and OS from distant recurrence: hazard ratio 0.991, p = 0.46. The median OS from distant recurrence was numerically longer among patients with a TDRI of ≥12 months (n = 103) than <12 months (n = 84) but not statistically significant (23.7 vs. 17.8 months, p = 0.47). The median duration of first-line trastuzumab-based regimens for patients previously treated with adjuvant trastuzumab and diagnosed with distant disease recurrence was 8.8 months (n = 88). This retrospective, exploratory study suggests that TDRI did not impact on OS measured from distant recurrence. We argue that prospective collection of treatment information beyond disease progression should be included in future clinical studies.